Designing a Prototype Coaching Model Based on Emotional Intelligence and Job Performance: A Case Study of Global Technology Group Company , Myanmar - Swe Hlaing, Min; Fernando, Maria Socorro C.L. (ABAC ODI JOURNAL Vision. Action. Outcome, 2021)
This research investigates the influence of emotional intelligence domains on job performance. The questionnaire is based on Emotional Intelligence's four domains as independent variables, namely: self-awareness, self-management, social awareness, and relationship management, and the dependent variable is job performance. Quantitative data using a questionnaire was gathered from a sample of 70 employees in the management, middle management, and supervisor levels working in Global Technology Group Company (GTG). Qualitative data was gathered from interviews of 12 employees. The results of the interview showed that employees recognize and control the positive outcome, Emotional intelligence helps motivation and career improvement, positive emotions keep a clear mind, understand well, and manage effectively, self-evaluation, listening to comments from coworkers, and observing how to treat them, job satisfaction in the relationship and job performance and target job accomplishment and work satisfaction on respective tasks. Moreover, the quantitative data results showed that self-management and relationship management's emotional intelligence domains influence job performance. The study recommends a coaching model that can be utilized to support self-awareness and relationship management for effective job performance.